CYTOKININS: SYNTHESIS, MASS SPECTRA, AND BIOLOGICAL ACTIVITY OF COMPOUNDS RELATED TO ZEATIN - Leonard, Nelson J. (1969)
Compounds related to dihydrozeatin that define the influence of the location of the hydroxyl group along the side chain have been synthesized and tested for cytokinin activity. The compounds compared are in the series: 6-(X-hydroxy-3-methylbutylamino)purines and their ribosides, where X = 2, 3, and 4. Hydroxy substitution on the 4-position of the side chain enhances, but in the 2-, 3-, or 2- and 3- positions, decreases cytokinin activity as compared with the unsubstituted isopentyl (or isopentenyl) chains. This differential influence of the position of the hydroxyl group in the N(6)-chain holds also for the similarly related 9-β-D-ribofuranosides. The relatively higher activity of 3,4-dihydroxy as compared with 2,3-dihydroxy derivatives is consistent with this position effect. Compounds related to zeatin possessing side-chain ester moieties have also been synthesized and tested comparatively. Among these, 6-(4-acetoxy-3-methyl-trans-2-butenylamino)purine is at least as active as zeatin, the most active presently known cytokinin in the tobacco bioassay, whereas the analog, methyl 2-methyl-4-(purin-6-ylamino)-trans-crotonate, with the ester function effectively reversed, has vastly lower activity, and its riboside is practically inactive.